The Effect of Adaptive Competency on Teamwork Effectiveness: The Mediating Effect of Cultural Adaptation - Enny Istanti; Wahyudi; Adriani Gunawan; Imelda Fatmawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Increasing workforce diversity requires organizations to strengthen effective multigenerational collaboration strategies. This study develops a culturally responsive competency framework for multigenerational teamwork and examines cultural adaptation as a mechanism linking adaptive competency to teamwork effectiveness. An exploratory sequential mixed-methods design was conducted in a technology company and an educational institution in Surabaya, Indonesia. Semi-structured interviews with six purposively selected informants identified three interrelated capabilities: cultural adaptation, value flexibility, and cross-generational empathy. These findings were used to contextualize the quantitative measures. Questionnaire data from 45 employees representing Baby Boomers, Generation X, Millennials, and Generation Z were analyzed using regression and bootstrap mediation. Adaptive competency was positively associated with teamwork effectiveness (β = 0.51, p < 0.001) and cultural adaptation (β = 0.50, p < 0.001). Cultural adaptation remained associated with teamwork effectiveness after adaptive competency was controlled (β = 0.35, p = 0.018). The indirect effect was significant (effect = 0.170, BootSE = 0.078, 95% CI [0.035, 0.342]), indicating partial mediation. The integrated findings show that adaptive competency supports teamwork when translated into culturally responsive communication and behavior. The study highlights the importance of adaptive communication, value flexibility, cross-generational empathy, and mentoring in diverse organizations.